Bipolar Disorder as Comorbidity with Sjögren's Syndrome: What Can We Do?. (11th September 2020) - Chebli, Selima; Zgueb, Yosra; Ouali, Uta; Taleb, Sana; Nacef, Fethi
Abstract : Neuropsychiatric manifestations in Sjögren's syndrome are common and can occur not only during its course, but also at the onset of the disease. Depression and anxiety were the most frequently described symptoms. However, the association with bipolar disorder seems to be rare and not well documented. This case report presents a patient with bipolar disorder as comorbidity with Sjögren's syndrome, suggesting that bipolar disorder could be associated with this autoimmune disease, which could lead to delaying diagnosis and treatment. A better analysis of the clinical background should be done by psychiatrists so to help early diagnosis and adapting prescription. Corticosteroids indicated in Sjögren's syndrome should be prescribed with caution in bipolar disorder.